Case Report: Intraneural Intracanalicular Ganglion Cyst of the Hypoglossal Nerve Treated by Extradural Transcondylar Approach - Bilgin-Freiert, Arzu; Fugleholm, Kåre; Poulsgaard, Lars (Journal of Neurological Surgery Reports, 2015)
We report a case of an intraneural ganglion cyst of the hypoglossal canal. The patient presented with unilateral hypoglossal nerve palsy, and magnetic resonance imaging showed a small lesion in the hypoglossal canal with no contrast enhancement and high signal on T2-weighted imaging. The lesion was assumed to be a cystic schwannoma of the hypoglossal nerve. Stereotactic irradiation was considered, but in accordance with the patient's wishes, surgical exploration was performed. This revealed that, rather than a schwannoma, the patient had an intraneural ganglion cyst, retrospectively contraindicating irradiation as an option. This case illustrates a very rare location of an intraneural ganglion cyst in the hypoglossal nerve. To our knowledge there are no previous reports of an intraneural ganglion cyst confined to the hypoglossal canal.
Keywords: intraneural ganglion cyst; hypoglossal nerve palsy; hypoglossal canal; transcondylar approach